Crosstalk suppression techniques for multi-channel regeneration based on fiber optic parametic amplifier - Ibrahim, Nor Zaidatun Nadrah (2015)
Optical transmission system is the best choice to transmit high capacity information over long distances. The progressive development in optical transmission technologies allows the growth of transmission speed and capacity.2R or 3R regeneration can refine the degraded signal and improve transmission performance. 2R stands for reamplifying and reshaping the signal, and 3R adds retiming of the signal. Conventionally, electrical repeaters are used for the regenerations. In this regeneration system, the signal is converted from optical to electrical, regenerated electrically and finally converted back to an optical. Besides the electrical repeater, all optical regenerator is an alternative to regenerate optical signal without the need of optical electrical optical signal conversions. All optical signal regeneration has been recognized as a potential enabler of future transparent long haul high bit rate systems. All optical regeneration is easily applicable to various modulations formats signals and can work ultrafast. Since fiber based all optical regeneration was introduced two decades ago, many excellent techniques to regenerate signals have been proposed was introduced in order to reduce nonlinear effect within the channel, two techniques approaches being polarization interleaving and polarization multiplexing. The purpose of the signal regeneration is therefore to remove these distortions and to restore the characteristics of the optical signal to a suitable level so that a high overall transmission quality is maintained. As a result, the improvement of Q factor of each regenerated channel can be more improved for each techniques. In this result, a WDM system with polarization based system is analyzed in order to mitigate the nonlinear effects within the fiber channel. Hence, the performance can be further improved by using concept of polarization modulation in the transmitter section WDM system.